DEVELOPING ENTREPRENEURIAL MINDSET THROUGH THE 'YOUNG LELEPRENEUR' COLLABORATIVE LEARNING MODEL AND CURRICULUM INTEGRATION AT CENDERAWASIH II SENIOR HIGH SCHOOL - Rusdiyanto, Edi; Soesanta, Prabawa Eka; Muna, Siti Umamah Naili; Munawir, Abdillah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
SMA Cenderawasih II in South Tangerang faces dual challenges, including students’ low understanding of nutrition and the economic limitations of their families. The Community Service Team from the Graduate School (SPS) of Universitas Terbuka (UT) took the initiative to implement a collaborative learning model called "Young Lelepreneur." This model was specifically designed by integrating catfish farming curriculum into school activities in close coordination with SMA Cenderawasih II. The community service program at SMA Cenderawasih II, South Tangerang, successfully enhanced students’ knowledge, skills, and entrepreneurial character through practice-based catfish farming activities (learning by doing). Through a series of preparation, technical training, and implementation stages, students not only gained a theoretical understanding of basic biology and fishery management but also applied it directly in the field from pond construction and feed management to water quality control. This activity strengthened the synergy between the school, the community service team, and the students in realizing contextual and applicable learning. Monitoring and evaluation results indicate that this program has the potential to become a practice-based learning model that can be integrated into entrepreneurship and applied biology curricula. Furthermore, the development plan of the "Young Lelepreneur" program serves as a strategic step toward creating an educational ecosystem focused on innovation, economic independence, and school community empowerment.